Diagnostic Value of Anthropometric Measurements for Familial Partial Lipodystrophy, Dunnigan Variety - Vasandani, Chandna (J Clin Endocrinol Metab, 2020)
CONTEXT: Familial partial lipodystrophy, Dunnigan variety (FPLD2) is a rare autosomal dominant disorder resulting from LMNA causal variants, which is characterized by loss of subcutaneous fat from the extremities and predisposition to metabolic complications. The diagnostic value of various anthropometric measurements for FPLD2 remains unknown. OBJECTIVE: To determine specificity and sensitivity of anthropometric measurements for the diagnosis of FPLD2. METHODS: We measured skinfold thickness and regional body fat by dual energy X-ray absorptiometry (DXA) in 50 adult females and 6 males with FPLD2 at UT Southwestern and compared their data with the sex- and age-matched controls from the National Health and Nutrition Examination Survey (NHANES) 1999-2010. We further compared data from 1652 unaffected females from the Dallas Heart Study and 23 females with FPLD2 from the National Institutes of Health with the NHANES data. RESULTS: The DXA-derived lower limb fat (%) had the best specificity (0.995) and sensitivity (1.0) compared with the upper limb fat, truncal fat, the ratio of lower limb to truncal fat, and triceps skinfold thickness for adult females with FPLD2. The lower limb fat below 1st percentile of NHANES females had a false-positive rate of 0.0054 and a false negative rate of 0. The diagnostic value of anthropometric parameters could not be determined for males with FPLD2 due to small sample size. CONCLUSIONS: The lower limb fat (%) is the best objective anthropometric measure for diagnosing FPLD2 in females. Women with below the 1st percentile lower limb fat should undergo genetic testing for FPLD2, especially if they have metabolic complications.